Cardiopulmonary resuscitation practices amid COVID-19 in four Gauteng public hospitals - Almien Smit; Andreas Engelbrecht; Suma Rajan (Journal of the Colleges of Medicine of South Africa)
Background: The coronavirus disease 2019 (COVID-19) pandemic challenged healthcare systems worldwide. Owing to the transmission with aerosol-generating procedures, cardiopulmonary resuscitation (CPR) practices were changed. Little is known about the adherence and/or uptake of these guidelines by healthcare workers (HCWs) in lower-middle income countries. This study seeks to describe the CPR practices among HCWs in South Africa.